First performance test of FeSe0.5Te0.5-coated conductor coil under high magnetic fields. (28th February 2023) - Wei, Shaoqing; Liu, Xiao; Zhang, Zhan; Liu, Fang; Qin, Jinggang; Shi, Yi; Li, Yijie; Liu, Linfei; Shi, ZhiXiang; Ren, Li; Xu, Ying; Duan, Pu; et al.
Abstract: Iron-based superconductors have attracted intense interest from scientists around the world. The first FeSe0.5 Te0.5 hybrid coil, including one FeSe0.5 Te0.5 single pancake coil (SPC) and eight YBCO double pancake coils (DPCs), was successfully fabricated and tested in this study. The FeSe0.5 Te0.5 tape used in the hybrid coil is encapsulated to strengthen the tape, and has a thickness of 0.15 mm and a width of 10.5 mm to withstand the high stress during the cold test. The FeSe0.5 Te0.5 encapsulated tape exhibits good performance in the 4.2 K cold test. YBCO DPCs were divided into two groups connected to both sides of the FeSe0.5 Te0.5 SPC. The critical current of the FeSe0.5 Te0.5 coil was measured as the background field increased from 0 T to 10 T. The transport critical current of the FeSe0.5 Te0.5 SPC was 108.1 A at self-field and 17.4 A at 10 T, which had almost the same performance as the FeSe0.5 Te0.5 tape. The results of this study showed that the FeSe0.5 Te0.5 -coated conductor coil has good performance in high magnetic fields.